2011
DOI: 10.3201/eid170310060
|View full text |Cite
|
Sign up to set email alerts
|

Nontuberculous Mycobacteria in Respiratory Tract Infections, Eastern Asia

Abstract: To characterize the distribution of nontuberculous mycobacteria (NTM) species isolated from pulmonary samples from persons in Asia and their association with pulmonary infections, we reviewed the literature. Mycobacterium avium complex bacteria were most frequently isolated (13%-81%) and were the most common cause of pulmonary NTM disease (43%-81%). Also pathogenic were rapidly growing mycobacteria (M. chelonae, M. fortuitum, M. abscessus). Among all NTM isolated from pulmonary samples, 31% (582/1,744) were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
79
3
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 172 publications
(93 citation statements)
references
References 28 publications
8
79
3
3
Order By: Relevance
“…Different subspecies may indicate divergent treatment plans, especially for those plans that involve clarithromycin (5,28,(46)(47)(48)(49)56). Consequently, development of a fast and accurate technique for the identification of M. abscessus subspecies is urgently needed.…”
Section: Discussionmentioning
confidence: 99%
“…Different subspecies may indicate divergent treatment plans, especially for those plans that involve clarithromycin (5,28,(46)(47)(48)(49)56). Consequently, development of a fast and accurate technique for the identification of M. abscessus subspecies is urgently needed.…”
Section: Discussionmentioning
confidence: 99%
“…Rather than focusing on results of VNTR typing, which are most likely independent of virulence factors and can thus be misleading, it is better to find these virulence factors and integrate them, as well as data on host genetics and immunological status, into patient diagnostics (548). Also, these observations stem from studies performed in East Asia; given the observed differences in clinical relevance and frequency of isolation of NTM species between East Asia and other regions (549,550), these findings remain to be validated in studies in other regions.…”
Section: What Does Typing Tell Us About Human Transmission Of Ntm Dismentioning
confidence: 99%
“…The increase in NTM infection may reflect the increase in number of transplants, the intensification of immune suppressive drugs, prolonged survival of transplant recipients, and/or improved diagnostic techniques. Although a few studies have reported on NTM infections in patients with hematological malignancy [5,[11][12][13], none of those studies investigated the clinical characteristics and outcome of NTM infection in patients with hematological malignancy.…”
Section: Introductionmentioning
confidence: 56%
“…The incidence of NTM infection among hematopoietic stem cell recipients ranged from 0.4% to 4.9% noted in previous studies [7][8][9][10]. Compared with the general population [3][4][5][6], patients with hematological malignancy have a significantly higher risk of In this study, rapidly growing mycobacteria (M. abscessus, M. fortuitum, M chelonae, 42%) were the most common isolates, followed by MAC (38%) and M. kansasii (18%). In the study by Doucette et al [7], 26 (27%) of 95 isolates were MAC and 43 (45%) of the 95 isolates were rapidly growing mycobacteria in hematopoietic stem cell recipients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation